STRUKTUR DAN PERAN ORGANISASI DALAM PENERAPAN GOOD CORPORATE GOVERNANCE - Salsabillah Zahwa Khairunnisa; Nurhalizah Bandaso; Muhammad Kurniawan Pulungan; Ahmad Wahyudi Zein (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study examines the role and organizational structure in supporting the implementation of Good Corporate Governance (GCG) amid accelerating globalization and technology that create intense business competition. Employing a library research method with descriptive qualitative analysis, the research synthesizes secondary data from ASEAN Corporate Governance Scorecard (ACGS) 2024-2025, OJK SNLIK reports, UGM studies, and BEI company cases such as BRI, Bank Mandiri, and Garuda Indonesia for the 2021-2025 period. Key findings reveal that the two-tier organizational structure (RUPS quorum 80%, independent Board of Commissioners 55%, risk-audit committees based on COSO) serves as a crucial mediator enhancing GCG effectiveness per OECD principles and POJK 21/2015, with strong correlation to ROE (r=0.62r=0.62, p<0.01) and 20-30% market cap increase in state-owned banks. However, persistent barriers including low executive GCG literacy (<50%), conflicts of interest in family firms (70-80% BEI), and weak internal controls (fraud triangle in Garuda case with 40% share price drop) underscore the need for a hybrid local GCG model based on gotong royong and ISO 37001. This research contributes to integrative agency-stewardship-institutional theory, recommending stronger OJK enforcement, 60%+ board independence, and primary SEM-PLS validation in North Sumatra for emerging markets GCG models.​